Shareholding Interest in Companies Listed on B3 in 2018: A Study of Networks - Caroline Alvarenga Carvalho (BBR - Brazilian Business Review, 2019)
The shareholding structure of large companies interferes with market competition, as well as the financial stability thereof. Some international studies have analyzed the control network of companies in their corresponding countries, others have broadened such vision to transnational companies, conducting a world level analysis, with both aiming to describe the willingness of the main shareholders regarding the network structure. Thus, the challenge herein is to elaborate and analyze the network of shareholding in companies listed on B3 in 2018. This paper will be descriptive research that uses Network Analysis of data obtained from Economatica software. As a result, we find a network with a giant component comprised of 726 players and a shareholders’ network of low density, high modularity and with main players of high influence. The results contribute to understanding the current structure of the Brazilian stock market share and are expected to encourage new researches on the Brazilian financial market.